2021
DOI: 10.1111/roiw.12514
|View full text |Cite
|
Sign up to set email alerts
|

Ex ante Inequality of Opportunity in Health among the Elderly in China: A Distributional Decomposition Analysis of Biomarkers

Abstract: We present a comprehensive analysis of ex ante inequality of opportunity (IOp) in health among Chinese adults aged 60+ and decompose the contributions of different sets of circumstances. Data are drawn from the 2011 and 2015 waves of the China Health and Retirement Longitudinal Study (CHARLS) linked with the 2014 CHARLS Life History Survey. We use a range of blood-based biomarkers, and apply a re-centered influence function (RIF) approach and a Shapley-Shorrocks decomposition to partition the contribution of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The findings underscore the importance of improving access to healthcare for children and enhancing the health and behaviors of parents in socioeconomically disadvantaged families to reduce health disparities in the Chinese population. Disparities among older adults in China are significantly influenced by geographic location and urban/rural distinctions, possibly due to unequal allocation of healthcare resources, primary healthcare services, and welfare support (9). Additionally, our study reveals that health inequality is influenced not only by age and gender but also by differences in childhood experiences.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The findings underscore the importance of improving access to healthcare for children and enhancing the health and behaviors of parents in socioeconomically disadvantaged families to reduce health disparities in the Chinese population. Disparities among older adults in China are significantly influenced by geographic location and urban/rural distinctions, possibly due to unequal allocation of healthcare resources, primary healthcare services, and welfare support (9). Additionally, our study reveals that health inequality is influenced not only by age and gender but also by differences in childhood experiences.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, utilizing distributional decompositions indicated that concentrating solely on mean-based decomposition would neglect crucial aspects associated with early-life conditions, notably when investigating disparities in household assets at the lower spectrum. This aspect is significant as individuals in this bracket are generally perceived as less healthy ( 10 ).…”
Section: Discussionmentioning
confidence: 99%